Melatonin potentiates the anti‐tumour effect of pravastatin in rat mammary gland carcinoma model. Issue 6 (30th September 2014) - Orendáš, Peter; Kubatka, Peter; Bojková, Bianka; Kassayová, Monika; Kajo, Karol; Výbohová, Desanka; Kružliak, Peter; Péč, Martin; Adamkov, Marián; Kapinová, Andrea; Adamicová, Katarína; Sadloňová, Vladimíra; et al.
Summary Previous studies in the field of cancer research have suggested a possible role for statins in the reduction of risk in certain malignancies. The purpose of these studies was to examine the chemopreventive effects of pravastatin alone and in combination with pineal hormone melatonin in the N‐methyl‐N‐nitrosourea‐induced mammary carcinogenesis model. Pravastatin was given orally (1 00 mg/kg) and melatonin was added to the water (20 μg/ml). Chemoprevention began seven days prior to carcinogen administration and subsequently continued for 15 weeks until autopsy. At autopsy, mammary tumours were removed and prepared for histopathological and immunohistochemical analysis. Parameters of experimental carcinogenesis, mechanism of action (biomarkers of apoptosis, angiogenesis and proliferation) and side effects after long‐term treatment in animals were assessed. Pravastatin alone suppressed tumour frequency by 20.5% and average tumour volume by 15% compared with controls. Combined administration of the drugs decreased tumour frequency by 69% and lengthened tumour latency by nine days compared with control animals. The ration between high and low grade carcinomas was apparently reduced in both treated groups. The analysis of carcinoma cells showed significant expression increase in caspase‐3 and caspase‐7 after pravastatin treatment; however, combined treatment even more pronounced increase in the expression of both caspases. Regarding VEGFR‐2 expression, a small effect in carcinomas of both treated groups was found. In plasma metabolism evaluation, pravastatin alone significantly decreased levels of glucose and triacylglycerols. Our results suggest a mild anti‐neoplastic effect of pravastatin in this rat mammary gland carcinoma model. Statins co‐administered with other suitable drug (e.g. melatonin) should be further evaluated for tumour‐preventive properties.